2017
DOI: 10.1017/s175173111600183x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of foal heat in female donkeys

Abstract: In this study, the first postpartum heat, termed the foal heat, characteristics and performance in female donkey (jenny) of Martina Franca are described. To this end, the follicular development of 42 jennies during foal heat was compared with that of 31 jennies at the third estrus after foaling. Estrus length (7.1 ± 0.9 and 6.8 ± 0.7 days), follicular development and preovulatory follicle size (43.7 ± 3.5 and 45.1 ± 2.5 mm) were similar between jennies during the foal heat and during the third estrus after foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
3
15
2
Order By: Relevance
“…Quaresma and Payan-Carreira (2015) reported a mean follicle diameter of 40.2 mm in single ovulations, 36.7 mm in double ovulations, and 38.6 mm in triple ovulations, when characterizing the estrous cycle of donkeys. This was similar to the results of Carluccio et al (2017), who obtained pre-ovulatory follicle diameter of up to 45.1 mm in postpartum estrous cycles for this species, without using an ovulation inducer. Both studies found higher mean follicle diameter values than the one obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Quaresma and Payan-Carreira (2015) reported a mean follicle diameter of 40.2 mm in single ovulations, 36.7 mm in double ovulations, and 38.6 mm in triple ovulations, when characterizing the estrous cycle of donkeys. This was similar to the results of Carluccio et al (2017), who obtained pre-ovulatory follicle diameter of up to 45.1 mm in postpartum estrous cycles for this species, without using an ovulation inducer. Both studies found higher mean follicle diameter values than the one obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Gestation lengths have been studied for a number of donkey breeds in recent years [12,34,35,38,[48][49][50] but not for Chinese breeds. The reported average gestation length ranges from 353 days [12] to 371 days [48][49][50]. The shortest and longest gestation are reported by Galisteo and Perez-Marin [35] as 331 and 421 days, respectively.…”
Section: Reproductive Performance Modelmentioning
confidence: 99%
“…Foal heat, the first heat after giving birth, usually occurs in the first two weeks after a jenny has given birth to a foal [51]. In donkeys, foal heat can be used successfully but with slightly lower conception rates than in the following cycles [38,49]. Secondly, the conception rates reported in the literature are mainly based on controlled research studies.…”
Section: Reproductive Performance Modelmentioning
confidence: 99%
See 2 more Smart Citations